Universal hospital admission screening for carbapenemase-producing organisms in a low-prevalence setting. (11th August 2016) - Otter, Jonathan A.; Dyakova, Eleonora; Bisnauthsing, Karen N.; Querol-Rubiera, Antonio; Patel, Amita; Ahanonu, Chioma; Tosas Auguet, Olga; Edgeworth, Jonathan D.; Goldenberg, Simon D.
Abstract : Background: Carbapenemase-producing Enterobacteriaceae (CPE) are an emerging threat for healthcare providers worldwide. Objectives: To determine CPE carriage rates and risk factors in an unselected hospital cohort at the time of admission. Methods: We approached 4567 patients within 72 h of admission to provide a rectal swab and answer a questionnaire on risk factors for carriage. Rectal swabs were cultured for carbapenem-resistant organisms on chromogenic and non-chromogenic agar, and tested for carbapenemase production by PCR (Check-Direct CPE). The study was approved by the NHS Research Ethics Committee. Results: Only 6 CPE were cultured from 5 (0.1%) of 4006 patients who provided a rectal swab; only 1 was cultured using non-chromogenic media. An additional 76 culture-negative rectal swabs were initially PCR positive, but none grew a carbapenem-resistant organism despite enrichment culture and only two were positive when retested several months later by Check-Direct and a second PCR assay (Cepheid GeneXpert ® Carba-R). A modified Ct cut-off of <35 would have resolved these apparent false-positives. 40% of patients had a risk factor that should prompt screening and pre-emptive isolation as defined by UK CPE guidelines but only 8.1% and 20.2% of these patients had been screened and pre-emptively isolated by clinical teams, respectively. Overseas hospitalization was the only significant risk factor for CPE carriage ( P < 0.001, OR 64.3, 95% CI 7.3–488.5). Conclusions: This study highlights a very low carriage rate of CPE. Hospitalization abroad is the most important risk factor to guide admission screening in this low-prevalence setting.